Managing the transformation of the global commons into luxuries for all - Cristini, Hélène; Kauppinen-Räisänen, Hannele (Elsevier, 2020)
In less than a century, mass industrialization and consumption have altered the Earth’s ecosystem and its resources. The elementary resources of the global commons—namely, air, water, and land—have been depleted, and human beings are increasingly suffering of various negative harms as a result of poor air quality, undrinkable water, and food contamination. Through the lens of the waste and scarcity of these elementary global commons, this study argues that luxury may relate to access to the elementary global commons and their resources. In doing so, this study introduces a new aspect of luxury and an alternative perspective to the prerequisites for human existence—namely, human needs of air, water, and food by reconsidering their existence in contemporary society. It explores the transformation of those human needs to becoming luxuries that goes beyond expensive products and services, and human yearning. The study contributes to current understandings of unconventional luxury.
Keywords: global commons; human well-being; natural resources; unconventional luxury; scarcity; waste and shortage; consumption; sustainable development; food; luxury; food production; consumer behaviour; natural resources; environmental pollution; luxury goods; multiculturalism; fi=Markkinointi|en=Marketing|